Extraction of cellulose nanofibers via eco-friendly supercritical carbon dioxide treatment followed by mild acid hydrolysis and the fabrication of cellulose nanopapers - Mohd Saad, Nurul Atiqah; Gopakumar, Deepu A.; Taiwo, Owolabi Folahan Abdulwahab; Pottathara, Yasir Beeran; Rizal, Samsul; N. A., Sri Aprilia; Hermawan, Dede; Md. Tahir, Paridah; Thomas, Sabu; H. P. Shawkataly, Abdul Khalil (MDPI, 2019)
The conventional isolation of cellulose nanofibers (CNFs) process involves high energy input which leads to compromising the pulp fiber’s physical and chemical properties, in addition to the issue of elemental chlorine-based bleaching, which is associated with serious environmental issues. This study investigates the characteristic functional properties of CNFs extracted via total chlorine-free (TCF) bleached kenaf fiber followed by an eco-friendly supercritical carbon dioxide (SC-CO2) treatment process. The Fourier transmission infra-red FTIR spectra result gave remarkable effective delignification of the kenaf fiber as the treatment progressed. TEM images showed that the extracted CNFs have a diameter in the range of 10–15 nm and length of up to several micrometers, and thereby proved that the supercritical carbon dioxide pretreatment followed by mild acid hydrolysis is an efficient technique to extract CNFs from the plant biomass. XRD analysis revealed that crystallinity of the fiber was enhanced after each treatment and the obtained crystallinity index of the raw fiber, alkali treated fiber, bleached fiber, and cellulose nanofiber were 33.2%, 54.6%, 88.4%, and 92.8% respectively. SEM images showed that amorphous portions like hemicellulose and lignin were removed completely after the alkali and bleaching treatment, respectively. Moreover, we fabricated a series of cellulose nanopapers using the extracted CNFs suspension via a simple vacuum filtration technique. The fabricated cellulose nanopaper exhibited a good tensile strength of 75.7 MPa at 2.45% strain.